Evolving landscapes: long term land use and climate-induced changes in the Brahmaputra floodplain, India - Saeed, Umar; Das, Rashmi; Ali, Sk Zeeshan; Mani, Ashish; Badola, Ruchi; Hussain, Syed Ainul (Frontiers in Environmental Science, 2025)
Land-use/land-cover change is an essential factor for understanding the ecological degradation of forests under threat from different climatic and human-mediated activities. This study investigates the biodiversity and ecological significance of Kaziranga Tiger Reserve, situated in the Brahmaputra floodplain of Assam, India, known for its rich flora and fauna. Despite its ecological importance and rich biodiversity, the reserve faces increasing threats from habitat fragmentation, human-wildlife conflict, poaching, and the impacts of climate change, necessitating a thorough examination of its ecological dynamics. This study assesses land-use land-cover changes from 1913 to 2023, by analyzing the impacts on biodiversity, and assessing the relationship between climate trends and habitat loss. The methods involving geometric and radiometric corrections of historical maps and satellite images, identified key LULC classes such as agriculture, forest, waterbodies, settlements and grasslands. Climate trends were analyzed using statistical methods, including the Theil-Sen estimator and Mann-Kendall test, to determine significant changes. The analysis indicated a 15% increase in agricultural land and a 10% decline in forest cover, primarily due to encroachment and habitat conversion for farming. Furthermore, the correlation study revealed that climatic variability, such as rainfall and soil moisture, significantly influenced habitat conversion, driving agricultural expansion while restricting grasslands. The study emphasizes the critical importance of management approaches that link ecological monitoring with climate resilience efforts, reaching the need for collaborative conservation initiatives to safeguard reserve’s unique biodiversity and maintain its ecological functions.